Penambang Sampan (Kajian Eksistensi Penambang Sampan di Kelurahan Dalam Bugis Pontianak Timur Kalimantan Barat) - Arkanudin Arkanudin; Desca Thea Purnama; Ignasia Debbye Batuallo (Ideas Publishing, 2022)
The existence of the Sampan Paddle Miner in the Dalam Bugis Village, East Pontinaka still persists, although the road and bridge infrastructure that connects this village to the city center is already available. The purpose of this study was to confirm the existence of rowboat miners so that they still survive. The method used is a descriptive analytical method with a qualitative approach,describing the state of the studied community as it is. The results showed that this profession was chosen because it did not require any skill or level of education, rowing skills and owning a canoe were sufficient. The perception of canoe miners is very positive, the work they are involved in is a decent job and does not look down on other jobs.